Effect of freeze–thaw cycles on carbon stocks of saline–alkali paddy soil. Issue 12 (1st December 2016) - Tang, Jie; Liang, Shuang; Li, Zhaoyang; Zhang, Hao; Lou, Yun; Wang, Jingjing
ABSTRACT: This study aims to provide basic data to support accurate estimation of carbon stocks and reveal the physicochemical factors that influence the carbon cycle in saline–alkali soils. Soil samples were collected during initial freezing, complete freezing, initial thawing and complete thawing stages. Levels of soil organic carbon (SOC), soil inorganic carbon (SIC), moisture, salinity, pH and available nitrogen were determined, and variations were observed during the freezing and thawing periods. Correlation analysis and regression analysis of carbon contents and physicochemical properties were performed. The results showed that freeze–thaw cycles have significant effects on carbon contents. The SOC content initially decreased in the freezing stage and then increased in the thawing stage. However, the SIC content initially increased in the freezing stage, decreased in the initial thawing stage and finally increased in the complete thawing stage. The migration and transformation of SOC and SIC were observed both temporally and spatially. SOC was positively correlated with available nitrogen, moisture and salinity and negatively correlated with pH; while SIC was negatively correlated with available nitrogen, moisture and salinity and positively correlated with pH. Among the factors evaluated, available nitrogen and salinity exerted the greatest effects on SOC and SIC contents, respectively.